An Analysis of Investment for Hajj Funds from Islamic Law Perspective - Fahmi, Annas Syam Rizal (AL-IKTISAB: Journal of Islamic Economic Law, 2017)
Being the largest Muslim country with some 250 million Muslims, Indonesia faces a huge demand from its citizens eager to perform Hajj and then it will impact to the huge of funds to perform Hajj (Pilgrim). Initially, any surplus funds held by the Department of Religion are supposed to be paid to the Islamic Community Perpetual Funds (Dana Abadi Umat). Currently, the government is now eyeing the country’s hajj (Muslim pilgrimage) fund as a potential source of infrastructure finance. By that araises some debate whether the hajj funds can be used or no to finance Indonesia infrastructure project. Therefore, the study intends to analyse the investment of hajj funds from Islamic law perspective. However, findings of the study are that the use of the hajj funds for investment is permissible in Islam with some condition such as the benefit gained from it is used for infrastructures abd facilities of hajj performance.